Torso RTK controls Capicua degradation by changing its subcellular localization. - Grimm, O.; Zini, V.S.; Kim, Y.; Casanova, J.; Shvartsman, S.Y.; Wieschaus, E. (Development, 2012)
The transcriptional repressor Capicua (Cic) controls multiple aspects of Drosophila embryogenesis and has been implicated in vertebrate development and human diseases. Receptor tyrosine kinases (RTKs) can antagonize Cic-dependent gene repression, but the mechanisms responsible for this effect are not fully understood. Based on genetic and imaging studies in the early Drosophila embryo, we found that Torso RTK signaling can increase the rate of Cic degradation by changing its subcellular localization. We propose that Cic is degraded predominantly in the cytoplasm and show that Torso reduces the stability of Cic by controlling the rates of its nucleocytoplasmic transport. This model accounts for the experimentally observed spatiotemporal dynamics of Cic in the early embryo and might explain RTK-dependent control of Cic in other developmental contexts.